2012
DOI: 10.1371/journal.pone.0046853
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Induces Apoptosis in Human Acute Myeloid Leukemia Cells via the Mitochondrial Pathway and Akt Inactivation

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy characterized by a rapid increase in the number of immature myeloid cells in bone marrow. Despite recent advances in the treatment, AML remains an incurable disease. Matrine, a major component extracted from Sophora flavescens Ait, has been demonstrated to exert anticancer effects on various cancer cell lines. However, the effects of matrine on AML remain largely unknown. Here we investigated its anticancer effects and underlying mechanisms on human AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 28 publications
9
132
0
Order By: Relevance
“…Conditioning with CTX had often been used in doses 100mg/kg (Rombouts et al, 2000b;Tan et al, 2012), and it had also been used in doses 20mg/kg (Zhang et al, 2012a). The dose of total body irradiation (TBI) depended on the mouse strains and also on the source and irradiator.…”
Section: Xenogeneic Transplantation and Assessment Of Engraftmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Conditioning with CTX had often been used in doses 100mg/kg (Rombouts et al, 2000b;Tan et al, 2012), and it had also been used in doses 20mg/kg (Zhang et al, 2012a). The dose of total body irradiation (TBI) depended on the mouse strains and also on the source and irradiator.…”
Section: Xenogeneic Transplantation and Assessment Of Engraftmentmentioning
confidence: 99%
“…and intravenous (i.v.) routes (Kiser et al, 2001;Zhang et al, 2012a;Zhang et al, 2012b). In recent years, Wang et al (Wang et al, 2012) reported a successful engraftment of human acute lymphoblastic leukemia cells in NOD/SCID mice via intrasplenic inoculation.…”
Section: Xenogeneic Transplantation and Assessment Of Engraftmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrine was also demonstrated to activate the p38 pathway and trigger caspase-dependent apoptosis by inducing the generation of ROS in non-small cell lung carcinoma (6). Matrine is able to inhibit cell proliferation and induce the apoptosis of acute myeloid leukemia cells via the mitochondrial pathway and Akt inactivation (7). Furthermore, the growth of MCF-7 breast cancer cells was also inhibited by matrine via the miR-21/PTEN/Akt pathway (8).…”
Section: Introductionmentioning
confidence: 98%
“…Matrine can also inhibit cell viability and induce cell apoptosis in human acute myeloid leukemia (AML) cells in a doseand time-dependent manner. After treatment with matrine, apoptosis in AML cells was induced by collapsing the mitochondrial membrane potential, inducing cytochrome c release from mitochondria, reducing the ratio of Bcl-2/Bax, increasing the activation of caspase-3, and decreasing the levels of p-Akt and p-ERK1/2 [20] . In K562 cells, matrine was shown to inhibit cell proliferation and induce apoptosis via the mitochondrial pathway in a time-and dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%